Using illusions to understand hallucinations: differences in perceptual performances on illusory figures may underscore specific visuoperceptual impairments in Parkinson’s disease - Cucca, Alberto; Manara, Claudia Virginia; Catalan, Mauro; Liccari, Marco; Antonutti, Lucia; Lombardo, Tiziana Maria Isabella; Cenacchi, Valentina; Rangan, Sophie; Mingolo, Serena; Crisafulli, Carmelo; Dore, Franca; Murgia, Mauro; et al. (Frontiers in Neuroscience, 2023)
Visual hallucinations are prevalent, potentially disabling symptoms of Parkinson’s Disease. Multiple impairments in bottom-up sensory processing and top-down perceptual modulation are implicated in the pathophysiology of these phenomena. In healthy individuals, visual illusions are elicited by illusory figures through parametric manipulations of geometrical configurations, contrast, color, or spatial relationships between stimuli. These illusory percepts provide insight on the physiologic processes subserving conscious and unconscious perception. In this exploratory, cross-sectional, controlled study, perceptual performance on illusory figures was assessed on 11 PD patients with hallucinations, 10 non-hallucinating PD patients, and 10 age-matched healthy individuals. In order to characterize potential neural substrates of perceptual performances, patients’ brain metabolic patterns on FDG PET were also analyzed. Illusions relying on attentional modulation and global perception were attenuated in PD patients without hallucinations. This pattern was no longer recognizable in hallucinating patients. Conversely, illusory effects normally counteracted by figure to background segregation and overlapping figures recognition were enhanced in PD patients with hallucinations. FDG PET findings further suggest that perceptual differences between PD patients might be linked to abnormal top-down perceptual modulation.